The Image of "Nation" and "People" in the Indonesianwac Corpus: A Corpus Linguistic Study - Robi’atul Muthmainnah; Tsanaa Mahara Haq; Mega Permatasari; Hikmah Aulia (Journal of Social Research, 2026)
The terms bangsa (nation) and rakyat (people) play a pivotal role as pillars of collective identity while simultaneously establishing political legitimacy. Both terms frequently appear in Indonesian socio-political discourse; however, the ideological nuances distinguishing their representations have not been extensively explored in depth. This study aims to reveal how the images of bangsa and rakyat are constructed in Indonesian discourse. The study employs a mixed quantitative and qualitative method using a corpus linguistics approach. This research utilizes data sourced from the IndonesianWaC corpus, accessed via SketchEngine, with the analysis limited to the top 50 collocates (determined by frequency and LogDice scores) as well as 50 relevant concordance lines for each lemma. The analysis focuses on three aspects: collocation patterns, observing lexical meaning associations; semantic prosody, identifying evaluative tendencies (positive or negative); and semantic preference, to map the semantic domains accompanying both words. This study is expected to provide empirical evidence regarding the dynamics of lexical usage that reflect power relations, societal attitudes, and identity construction in the Indonesian language.